Governing and Managing Knowledge in Asia (World Scientific Publishing, 2005)
The spread of knowledge is a significant consequence of the process of globalization. Knowledge is used to tackle very diverse issues such as development challenges in emerging markets or the perplexity of corporate decision-makers in the business world. The creation and proper governance of actionable knowledge and intellectual capital have become key preconditions for sustained societal and corporate competitiveness in an era of rapid globalization. This represents new opportunities and challenges for policy makers, business leaders, managers and employees in both public and private sector organizations.